Evaluating the association between lipidome and female reproductive diseases through comprehensive Mendelian randomization analyses - Ye Ma; Fang Wu; Zeming Yu; Lu Yang (Scientific Reports)
Abstract This study aimed to assess the causal relationship between lipidome and female reproductive diseases (FRDs) using an advanced series of Mendelian randomization (MR) methods. This study utilized genome-wide association study (GWAS) summary statistics encompassing 179 lipidomes and six prevalent FRDs, namely polycystic ovary syndrome (PCOS), endometriosis, uterine fibroid, female infertility, uterine endometrial cancer, and ovarian cancer. The two-sample MR (TSMR) approach was employed to investigate the causal relationships, with further validation using false discovery rate (FDR) and multivariable MR (MVMR) methods. Subsequently, a range of comprehensive evaluations were performed, including sensitivity analysis, mediation MR analysis, reverse MR analysis, and steiger test. Examining 179 lipidome traits as exposures and 6 FRDs as outcomes, this study identified significant causal effects of 56 lipids on FRDs. Following multiple testing correction and MVMR validation, sphingomyelin (d38:2) was found to have a protective effect against PCOS (β = -0.104, 95% CI: -0.199 ~ -0.010, P = 0.031). Phosphatidylcholine (18:0_22:6) was associated with a decreased risk of developing uterine fibroid (β = -0.111, 95% CI: -0.201~ -0.021, P = 0.016), and sterol ester (27:1/20:3) showed significance in uterine endometrial cancer (β = -0.248, 95% CI: -0.443 ~ -0.053, P = 0.013). Conversely, phosphatidylethanolamine (18:2_0:0) was associated with increased risk of endometriosis (β = 0.183, 95% CI: 0.015 ~ 0.350, P = 0.033), while sterol ester (27:1/18:1) posed a risk influence on uterine fibroid (β = 1.007, 95% CI: 0.925 ~ 1.089, P < 0.001), and phosphatidylcholine (16:0_22:6) on uterine endometrial cancer (β = 0.229, 95% CI: 0.039 ~ 0.420, P = 0.018). Furthermore, it was determined that the causal associations between these lipidome profiles and FRDs were independent of BMI, obesity, diabetes, smoking, alcohol use, physical activity, inflammation, depression, waist-hip ratio, vitamin D, dehydroepiandrosterone sulphate, sex hormone binding globulin, and testosterone levels. Most outcomes passed consistent tests without evidence of heterogeneity, pleiotropy, or reverse causality. The results indicated a close association between specific lipidomes, particularly sphingomyelin, lysophosphatidylethanolamine, cholesterol ester, and phosphatidylcholines, with FRDs. These lipid species may potentially serve as biomarkers and future drug targets for the treatment of FRDs.